Dark Passage: Mental Health Consequences of Parental Death - Petri Böckerman; Mika Haapanen; Christopher Jepsen (Institute of Labor Economics (IZA), 2021)
This paper studies the causal effect of parental death on children's mental health. Combining several nationwide register-based data for Finnish citizens born between 1971 and 1986, we use an event study methodology to analyze hospitalization for mental health-related reasons by the age of 30. We find that there is no clear evidence of increased hospitalization following the death of a parent of a different gender, but there are significant effects for boys losing their fathers and girls losing their mothers. Depression is the most common cause of hospitalization in the first three years following paternal death, whereas anxiety and, to a lesser extent, self-harm are the most common causes five to ten years after paternal death. We also provide descriptive evidence of an increase in the use of mental health-related medications and sickness absence, as well as substantial reductions in years of schooling, employment, and earnings in adulthood for the affected children.
Keywords: I10; I12; J12; J13; 330; parental death; mental health; hospitalization; depression; labor market